Automatized system of control and monitoring of gases from coal mines - Carreño Bodensiek, Carlos Guillermo (Universidad Pedagógica y Tecnológica de Colombia, 2010)
The present article describes the development of a system of monitoring and control of the principal gases that take place to the interior of the coal mines. This development is based on an application of the virtual instrumentation. It divides in three fundamental parts: the acquisition of the real time information of each one of the gases to controlling, secondly the design of the system of monitoring that consists of an application of software that there allows the adjustment of the permissible ranges of the gases and the generation of reports of control and finally the system of control of the ventilation, to reduce the critical levels of gases that they harm to the personnel of work. This research work in the area of technological application does there divide the projects realized by the research group GENTE, of theSchoolofElectromechanical Engineering, UPTC - Duitama.